Differential effects of ethnic density on the risk of postnatal depression and personality dysfunction. (January 2016) - Du Preez, Andrea; Conroy, Susan; Pawlby, Susan; Moran, Paul; Pariante, Carmine M.
Abstract : Background: The relationship between ethnic density and psychiatric disorder in postnatal women in the UK is unclear. Aims: To examine the effect of own and overall ethnic density on postnatal depression (PND) and personality dysfunction. Method: Multilevel analysis of ethnically mixed community-level data gathered from a sample of 2262 mothers screened at 6 weeks postpartum for PND and personality dysfunction. Results: Living in areas of higher own ethnic density was protective against screening positive for PND in White women ( z =–3.18, P = 0.001), even after adjusting for area level deprivation, maternal age, relationship status, screening positive for personality dysfunction, parity and geographical clustering (odds ratio (OR) 0.98 (95% CI 0.96–0.99); P = 0.002), whereas the effect on personality dysfunction ( z =–2.42, P = 0.016) was no longer present once the effect of PND was taken into account (OR = 0.99 (95% CI 0.90–1.0); P = 0.13). No overall ethnic density effect was found for women screening positive for PND or personality dysfunction. Conclusions: In White women, living in areas of higher own ethnic density was protective against developing PND.